Eksplorasi Pendidikan Inklusif: Kesetaraan dalam Pembelajaran - Saiful Bahri; Nuryati Nuryati (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2023)
Equality in learning at Kebangsaan Junior High School with an inclusive education approach. This research employs a qualitative method, including interviews, observations, and Focus Group Discussions (FGD) involving discussions with teachers and students at Kebangsaan Junior High School. The findings of this research indicate that gender equality issues remain a concern within the school environment. Students express experiences related to gender stereotypes, while teachers note challenges in implementing an inclusive approach. School administrators play a role in ensuring the success of inclusive education through supportive policies. To achieve the effectiveness of inclusive education, individual awareness, responsibility, mutual respect, and ongoing training for teachers and school staff are crucial. Thus, inclusive education aims not only to reduce gender discrimination but also to create a learning environment that is safe, comfortable, and supportive of cognitive development for students.